Alginic acid polysaccharide conductive polymer material as well as preparation method and application thereof in wound healing
Through sodium alginate, PEDOT: PSS and calcium ionic alginic acid polysaccharide conductive polymer materials, the problem of cumbersome operation, poor bio -degradation and insufficient conductivity of existing wounds, lack of conductivity, and lack of conductivity. Organize regeneration.
Patent Information
- Application Number
- CN202411399249.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing wound repair dressings have complicated procedures, poor biodegradability and insufficient electrical conductivity, which cannot effectively promote wound healing.
By crossing sodium alginate, clustering (3,4-ethylene ethylene polyne) -Cocystal sulfonate (PEDOT: PSS) to combine with calcium ions to prepare a kind of algina polysaccharide conductive polymer material. This material has Excellent biocompatibility and conductivity.
This material can stop bleeding, absorb the wound effusion, keep the wound moist, and significantly promote wound healing, and will not adhere to the wound tissue. Remoraling the material will not cause secondary damage to the surface of the wound.
Smart Images

Figure CN119367580A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of medical supplies, and particularly relates to an alginate polysaccharide conductive polymer material and a preparation method thereof and application in wound healing, particularly in the field of chronic wound healing and tissue regeneration. Background Art
[0002] Polysaccharides are the most abundant resources in nature, with significant biological activity, no obvious adverse reactions, good biocompatibility and degradability. Sodium alginate, as a natural polysaccharide polymer, has good affinity. When wound exudate comes into contact with sodium alginate, due to the interaction between biological fluids and ions, sodium alginate will slightly dissolve to produce a gel matrix, which helps protect the wound from the influence of microorganisms and provide a moist wound environment; it also helps to promote cell proliferation and tissue granulation formation, thereby promoting wound healing. Hydrogels are three-dimensional networks formed by cross-linking hydrophilic polymer chains with good biological properties. Alginate is known for its ability to form hydrogels through ionic crosslinking. Due to the ionic interaction between calcium ions and sodium alginate, sodium alginate ion-crosslinked hydrogels will spontaneously form anisotropic capillary structures. The network structure of the hydrogel and the 90% water content also provide space and ion migration capabilities for calcium ions and chloride ions. The free state of calcium ions can greatly reduce resistance, and its rapid movement can enhance conductivity.
[0003] Conductive polymers are long-chain polymers composed of carbon atoms and conjugated electron systems. After removing an electron from the eigenstate conjugated π orbital, the dispersed π electrons act as electron carriers and move freely along the unsaturated backbone to perform effective electron transfer, thereby achieving the conductive function. Conductive hydrogels are currently prepared by doping conductive polymers, and soft, stretchable biological tissues and conductive devices are integrated to achieve the effect of promoting wound healing. Conductive hydrogels have become an ideal substitute for traditional metal electrodes at the bioelectronic interface due to their unique biological tissue similarity and conductivity. There are many types of wound repair dressings on the market, but most of them have cumbersome operating steps, poor biodegradability and insufficient conductivity, which limit their biological applications. Materials with insufficient electrical activity may not provide sufficient electrical signals to promote healing. Therefore, it is critical to develop a material that is biosafe, sufficiently electrically active and promotes wound healing. Summary of the invention
[0004] In order to overcome the above-mentioned shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide an alginate polysaccharide conductive polymer material.
[0005] The alginate polysaccharide conductive polymer material of the present invention is obtained by cross-linking sodium alginate, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS) and calcium ions, has excellent biocompatibility, can stop bleeding, absorb wound fluid, keep wounds moist, promote wound healing and other multiple functions, and will not adhere to wound tissue. Removing the polymer material will not cause secondary damage to the wound surface.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned alginate polysaccharide conductive polymer material. The method for preparing the alginate polysaccharide conductive polymer material of the present invention is simple, the raw materials are cheap and readily available, the synthesis conditions are mild, the production route is concise, the process flow is simple, the operability is strong, the production quality is easier to control, and the obtained product has higher safety and clinical use value compared with existing similar products.
[0007] Another object of the present invention is to provide applications of the above-mentioned alginate polysaccharide conductive polymer material, especially in the field of chronic wound healing and tissue regeneration.
[0008] The purpose of the present invention is achieved through the following solutions:
[0009] The invention discloses an alginate polysaccharide conductive polymer material, which is obtained by cross-linking reaction of sodium alginate, poly (3,4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS) and calcium carbonate.
[0010] Preferably, the mass ratio of the sodium alginate, PEDOT:PSS and calcium carbonate may be (5-30):(1-13):(0.5-4).
[0011] Preferably, the degree of polymerization of the sodium alginate may be 80-750.
[0012] Preferably, the content of sodium alginate in the material is 0.5-3.0 wt%.
[0013] After the alginate polysaccharide conductive polymer material of the present invention is cross-linked with sodium alginate, PEDOT:PSS and calcium carbonate to obtain a gel, a calcium ion solution can be further coated on the surface of the gel for further cross-linking to obtain a hydrogel with further cross-linked surface.
[0014] Preferably, the gel can be coated on one side or both sides as required; more preferably, it is coated on one side.
[0015] Preferably, the calcium ion solution can be obtained by dissolving a soluble calcium salt commonly used in the art in water, such as calcium chloride, calcium sulfate, calcium gluconate, and the like.
[0016] Preferably, the concentration of calcium ions in the calcium ion solution is preferably 0.05-0.6 mol / L.
[0017] Preferably, the coating can be carried out by spraying, smearing or other conventional methods to cover the surface of the hydrogel with the calcium ion solution.
[0018] The present invention also provides a method for preparing the above-mentioned alginate polysaccharide conductive polymer material, comprising mixing sodium alginate, PEDOT:PSS and calcium carbonate in a water system to obtain a mixed solution, placing the mixed solution in a mold for cross-linking to obtain a sodium alginate-PEDOT:PSS-calcium ion hydrogel.
[0019] Preferably, sodium alginate may be first dissolved in water to obtain a solution having a sodium alginate mass concentration of 5 g / L-30 g / L, and then PEDOT:PSS and calcium carbonate solid may be added and mixed therewith.
[0020] Preferably, in the mixed solution, the mass concentration of PEDOT:PSS may be 1 g / L-13 g / L.
[0021] Preferably, in the mixed solution, the mass concentration of calcium carbonate may be 0.5 g / L-4 g / L.
[0022] Preferably, the cross-linking temperature may be 4° C.-25° C., and the cross-linking time may be 12 h-24 h.
[0023] Furthermore, after the sodium alginate-PEDOT:PSS-calcium ion hydrogel is cross-linked in the mold, a calcium ion solution with a calcium ion concentration of 0.05-0.6 mol / L can be coated on the surface of the hydrogel before demolding. After static cross-linking, an alginate polysaccharide conductive polymer material with further cross-linked surface is obtained.
[0024] Preferably, the gel can be coated on one side or both sides as required; more preferably, it is coated on one side.
[0025] Preferably, the amount of the calcium ion solution used is 0.01-0.03 times the volume of the sodium alginate-PEDOT:PSS-calcium ion hydrogel.
[0026] Preferably, static crosslinking can be performed at 20° C.-25° C., and the crosslinking time can be 1 s-10 s.
[0027] Preferably, after static cross-linking, the surface of the gel can be washed and the surface moisture can be dried to further obtain the target gel.
[0028] The preparation method of the present invention has cheap and readily available raw materials, mild synthesis conditions, a concise production route, a simple process flow, strong operability, and easier control of production quality. The obtained polymer material has higher safety and clinical use value compared with existing similar products.
[0029] The alginate polysaccharide conductive polymer material of the present invention is obtained by cross-linking sodium alginate, PEDOT:PSS and calcium ions, has excellent biocompatibility, can stop bleeding, absorb wound fluid, keep wounds moist, promote wound healing and other multiple functions, and will not adhere to wound tissue. Removal of the polymer material will not cause secondary damage to the wound surface. It can be applied to the fields of chronic wound healing and tissue regeneration, especially in the preparation of skin wound healing dressings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0031] Figure 1-Figure 2 This is a scanning electron microscope image of the alginate polysaccharide conductive polymer material prepared in Example 1.
[0032] Figure 3 This is the energy dispersive X-ray spectrum of the alginate polysaccharide conductive polymer material prepared in Example 1.
[0033] Figure 4 This is the swelling curve of the alginate polysaccharide conductive polymer material prepared in Example 1.
[0034] Figure 5 This is the cyclic compression curve of the alginate polysaccharide conductive polymer material prepared in Example 1. Cycle 1 represents one compression, and cycle 5 represents five cyclic compressions.
[0035] Figure 6 It is the strain scanning curve of the alginate polysaccharide conductive polymer material prepared in Example 1. Wherein, SA-Ca-PEDOT:PSS / Ca G' represents the storage modulus of the alginate polysaccharide conductive polymer material, and SA-Ca-PEDOT:PSS / Ca G" represents the loss modulus of the alginate polysaccharide conductive polymer material.
[0036] Figure 7 This is the alternating strain scanning curve of the alginate polysaccharide conductive polymer material prepared in Example 1. Wherein, SA-Ca-PEDOT:PSS / Ca G' represents the storage modulus of the alginate polysaccharide conductive polymer material, and SA-Ca-PEDOT:PSS / CaG" represents the loss modulus of the alginate polysaccharide conductive polymer material.
[0037] Figure 8 The electrical conductivity of the alginate polysaccharide conductive polymer materials prepared in Example 1, Example 2 and Example 3.
[0038] Fig. 9 The results of wound healing test. Among them, SA-Ca-PEDOT:PSS / Ca represents alginate polysaccharide conductive polymer material. DETAILED DESCRIPTION
[0039] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto. The materials involved in the following examples can be obtained from commercial channels unless otherwise specified. The methods described are conventional methods unless otherwise specified.
[0040] The invention provides an alginate polysaccharide conductive polymer material, which is obtained by cross-linking reaction of sodium alginate, poly (3, 4-ethylenedioxythiophene)-polystyrene sulfonate (PEDOT:PSS) and calcium carbonate.
[0041] In the present invention, the mass ratio of sodium alginate, PEDOT:PSS and calcium carbonate can be (5-30):(1-13):(0.5-4). In one embodiment, the mass ratio of sodium alginate, PEDOT:PSS and calcium carbonate is 5:1:0.5; in another embodiment, the mass ratio of sodium alginate, PEDOT:PSS and calcium carbonate is 15:6:2; in another embodiment, the mass ratio of sodium alginate, PEDOT:PSS and calcium carbonate is 30:13:4.
[0042] In the present invention, the degree of polymerization of the sodium alginate may be 80-750. In one embodiment, the degree of polymerization of the sodium alginate is 100-700.
[0043] In the present invention, the content of sodium alginate in the material is the amount used in conventional hydrogels, such as 0.5-3.0wt%. In one embodiment, the content of sodium alginate in the material is 0.5wt%; in another embodiment, the content of sodium alginate in the material is 1.5wt%; in another embodiment, the content of sodium alginate in the material is 3wt%.
[0044] In the present invention, the PEDOT:PSS is a conductive polymer, which mainly provides a conductive path for the cell's own bioelectricity and promotes signal transmission in the form of assisting endogenous bioelectric conduction. Conductive polymers essentially work by changing the bioelectric field of cells. Electrical stimulation promotes nerve regeneration by promoting the polarization of macrophages from M1 phenotype to M2 phenotype, promoting cell proliferation and migration, and then promoting epithelialization and nerve regeneration. The present invention cross-links PEDOT:PSS with calcium ions and sodium alginate, which can be concentrated locally in the wound during wound treatment, effectively exerting the electrical activity of PEDOT:PSS and its effects on wound healing, skin tissue regeneration, etc.
[0045] In the present invention, the calcium carbonate used is basically insoluble in water. Compared with the traditional method of forming gel by metal ion solution such as calcium chloride solution and sodium alginate, the present invention uses calcium carbonate to form gel with PEDOT:PSS and sodium alginate. Under the acidic conditions of PEDOT:PSS, calcium carbonate gradually releases dissociated calcium ions to cross-link with PEDOT:PSS and sodium alginate. The resulting cross-linked network structure is more uniform and flexible, and the mutual bonding is more firm, which greatly improves the mechanical properties and structural stability of the resulting gel material.
[0046] After the alginate polysaccharide conductive polymer material of the present invention is cross-linked with sodium alginate, PEDOT:PSS and calcium carbonate to obtain a gel, a calcium ion solution can be further coated on the surface of the gel for further cross-linking to obtain a hydrogel with further cross-linked surface.
[0047] In the present invention, the gel may be coated on one side or both sides as required; more preferably, it is coated on one side.
[0048] In the present invention, the calcium ion solution can be obtained by dissolving a soluble calcium salt commonly used in the art in water, such as calcium chloride, calcium sulfate, calcium gluconate, etc. In one embodiment, the calcium ion solution is a calcium chloride aqueous solution; in another embodiment, the calcium ion solution is a calcium sulfate aqueous solution; in another embodiment, the calcium ion solution is a calcium gluconate aqueous solution.
[0049] In the present invention, the concentration of calcium ions in the calcium ion solution is preferably 0.05-0.6 mol / L. In one embodiment, the concentration of calcium ions in the calcium ion solution is 0.05 M; in another embodiment, the concentration of calcium ions in the calcium ion solution is 0.2 M; in another embodiment, the concentration of calcium ions in the calcium ion solution is 0.5 M.
[0050] In the present invention, the coating can be carried out by spraying, smearing or other conventional methods to cover the surface of the hydrogel with the calcium ion solution. In one embodiment, the coating can be carried out by spraying to cover the surface of the hydrogel with the calcium ion solution; in another embodiment, the coating can be carried out by smearing to cover the surface of the hydrogel with the calcium ion solution.
[0051] The present invention also provides a method for preparing the above-mentioned alginate polysaccharide conductive polymer material, comprising mixing sodium alginate, PEDOT:PSS and calcium carbonate in a water system to obtain a mixed solution, placing the mixed solution in a mold for cross-linking to obtain a sodium alginate-PEDOT:PSS-calcium ion hydrogel.
[0052] In the present invention, sodium alginate can be first dissolved in water to obtain a solution with a sodium alginate mass concentration of 5g / L-30g / L, and then mixed with PEDOT:PSS and calcium carbonate. In one embodiment, the sodium alginate mass concentration in the solution is 5g / L; in another embodiment, the sodium alginate mass concentration in the solution is 15g / L; in another embodiment, the sodium alginate mass concentration in the solution is 30g / L.
[0053] In the present invention, sodium alginate may be first dissolved in water to obtain a sodium alginate solution, which is then mixed with PEDOT:PSS and stirred evenly, and finally calcium carbonate is added and stirred evenly to obtain the mixed solution.
[0054] In the present invention, the mass concentration of PEDOT:PSS in the mixed solution may be 1 g / L-13 g / L. In one embodiment, the mass concentration of PEDOT:PSS is 1 g / L; in another embodiment, the mass concentration of PEDOT:PSS is 6 g / L; in yet another embodiment, the mass concentration of PEDOT:PSS is 13 g / L.
[0055] In the present invention, the mass concentration of calcium carbonate in the mixed solution can be 0.5 g / L-4 g / L. In one embodiment, the mass concentration of calcium carbonate is 0.5 g / L; in another embodiment, the mass concentration of calcium carbonate is 2 g / L; in another embodiment, the mass concentration of calcium carbonate is 4 g / L.
[0056] In the present invention, the cross-linking temperature may be 4° C.-25° C., and the cross-linking time may be 12 h-24 h.
[0057] In the present invention, after sodium alginate-PEDOT:PSS-calcium ion hydrogel is cross-linked in a mold, a calcium ion solution with a calcium ion concentration of 0.05-0.6 mol / L can be coated on the surface of the hydrogel before demolding, and after static cross-linking, an alginate polysaccharide conductive polymer material with further cross-linked surface is obtained.
[0058] In the present invention, the amount of calcium ion solution used is 0.01-0.03 times the volume of sodium alginate-PEDOT:PSS-calcium ion hydrogel. In one embodiment, it is 0.01 times; in another embodiment, it is 0.02 times; in another embodiment, it is 0.03 times.
[0059] In the present invention, static crosslinking can be performed at 20° C.-25° C., and the crosslinking time can be 1 s-10 s.
[0060] In the present invention, after static cross-linking, the surface of the gel can be washed and the surface moisture can be dried to further obtain the target gel.
[0061] In the present invention, the gel may be coated on one side or both sides as required; more preferably, it is coated on one side.
[0062] In the present invention, the stirring is preferably magnetic stirring at room temperature, the rotation speed of the magnetic stirring is preferably 600 rpm, and the stirring time is the same or different and is preferably 10 h to 14 h.
[0063] The preparation method of the present invention has cheap and readily available raw materials, mild synthesis conditions, a concise production route, a simple process flow, strong operability, and easier control of production quality. The obtained polymer material has higher safety and clinical use value compared with existing similar products.
[0064] The alginate polysaccharide conductive polymer material of the present invention is obtained by cross-linking sodium alginate, PEDOT:PSS and calcium ions, has excellent biocompatibility, can stop bleeding, absorb wound fluid, keep wounds moist, promote wound healing and other multiple functions, and will not adhere to wound tissue. Removal of the polymer material will not cause secondary damage to the wound surface. It can be applied to the fields of chronic wound healing and tissue regeneration, especially in the preparation of skin wound healing dressings.
[0065] The present invention has no special limitation on the preparation method of the skin wound healing dressing, and the preparation method of the corresponding dressing can be used. The present invention has no special limitation on the existence form and amount of the alginate polysaccharide conductive polymer material in the skin wound dressing, and the conventional existence form and amount in the dressing can be used.
[0066] In the present invention, all reagents in the following examples and test examples are commercially available unless otherwise specified, and are chromatographically pure or analytically pure. The amount of each component is measured by mass and volume, g, mL.
[0067] Example 1
[0068] (1) 1.5 parts by mass of sodium alginate with a degree of polymerization of 100-700 is dissolved in 100 parts by volume of deionized water to obtain a sodium alginate solution, 0.6 parts by mass of PEDOT:PSS is mixed with the sodium alginate solution and stirred evenly, and magnetically stirred at room temperature for 12 hours to obtain a sodium alginate-PEDOT:PSS solution;
[0069] (2) dispersing 0.2 parts by weight of calcium carbonate powder in the above sodium alginate-PEDOT:PSS solution and stirring evenly to obtain a sodium alginate-PEDOT:PSS-calcium carbonate mixed solution;
[0070] (3) Pour the above mixed solution into The mixture was placed in a mold and cross-linked at 4°C for 24 h to obtain sodium alginate-PEDOT:PSS-calcium ion hydrogel (SA-Ca-PEDOT:PSS);
[0071] (4) dissolving calcium chloride in water to prepare a solution with a calcium ion concentration of 0.1 M;
[0072] (5) Spray a calcium chloride solution 0.02 times the volume of the hydrogel on the surface of the sodium alginate-PEDOT:PSS-calcium ion hydrogel. After cross-linking for 3 seconds, demold the gel, rinse the surface with deionizer, and use filter paper to absorb the moisture on the surface of the hydrogel to obtain a sodium alginate polysaccharide conductive polymer material (SA-Ca-PEDOT:PSS / Ca).
[0073] Example 2
[0074] (1) 1 part by mass of sodium alginate with a degree of polymerization of 100-700 is dissolved in 100 parts by volume of deionized water to obtain a sodium alginate solution, 0.2 parts by mass of PEDOT:PSS is mixed with the sodium alginate solution and stirred evenly, and magnetically stirred at room temperature for 12 hours to obtain a sodium alginate-PEDOT:PSS solution;
[0075] (2) dispersing 0.01 parts by weight of calcium carbonate powder in the above sodium alginate-PEDOT:PSS solution and stirring evenly to obtain a sodium alginate-PEDOT:PSS-calcium carbonate mixed solution;
[0076] (3) Pour the mixed solution into The mold was cross-linked at 25°C for 24 hours to obtain sodium alginate-PEDOT:PSS-calcium ion hydrogel;
[0077] (4) dissolving calcium chloride in water to prepare a solution with a calcium ion concentration of 0.05 M;
[0078] (5) Spray a calcium chloride solution 0.01 times the volume of the hydrogel on the sodium alginate-PEDOT:PSS-calcium ion hydrogel. After cross-linking for 3 seconds, demold the gel, rinse the surface with deionizer, and use filter paper to absorb the moisture on the surface of the hydrogel to obtain a sodium alginate polysaccharide conductive polymer material (SA-Ca-PEDOT:PSS / Ca).
[0079] Example 3
[0080] (1) 3 parts by mass of sodium alginate with a degree of polymerization of 100-700 is dissolved in 100 parts by volume of deionized water to obtain a sodium alginate solution, 1.3 parts by mass of PEDOT:PSS is mixed with the sodium alginate solution and stirred evenly, and magnetically stirred at room temperature for 12 hours to obtain a sodium alginate-PEDOT:PSS solution;
[0081] (2) dispersing 0.4 parts by weight of calcium carbonate powder in the above sodium alginate-PEDOT:PSS solution and stirring evenly to obtain a sodium alginate-PEDOT:PSS-calcium carbonate mixed solution;
[0082] (3) Pour the mixed solution into The mixture was placed in a mold and cross-linked at 4°C for 12 h to obtain sodium alginate-PEDOT:PSS-calcium ion hydrogel (SA-Ca-PEDOT:PSS).
[0083] (4) dissolving calcium chloride in water to prepare a solution with a calcium ion concentration of 0.2 M;
[0084] (5) Spray a calcium chloride solution 0.03 times the volume of the hydrogel on the sodium alginate-PEDOT:PSS-calcium ion hydrogel, remove it after cross-linking for 5 seconds, rinse it with deionizer, and use filter paper to absorb the moisture on the surface of the hydrogel to obtain a sodium alginate polysaccharide conductive polymer material (SA-Ca-PEDOT:PSS / Ca).
[0085] Example 4
[0086] (1) 1.5 parts by mass of sodium alginate with a degree of polymerization of 100-700 is dissolved in 100 parts by volume of deionized water to obtain a sodium alginate solution, 0.6 parts by mass of PEDOT:PSS is mixed with the sodium alginate solution and stirred evenly, and magnetically stirred at room temperature for 12 hours to obtain a sodium alginate-PEDOT:PSS solution;
[0087] (2) dispersing 0.2 parts by weight of calcium carbonate powder in the above sodium alginate-PEDOT:PSS solution and stirring evenly to obtain a sodium alginate-PEDOT:PSS-calcium carbonate mixed solution;
[0088] (3) Pour the above mixed solution into The mixture was placed in a mold and cross-linked at 4°C for 24 h to obtain sodium alginate-PEDOT:PSS-calcium ion hydrogel (SA-Ca-PEDOT:PSS);
[0089] (4) dissolving calcium gluconate in water to prepare a solution with a calcium ion concentration of 0.15;
[0090] (5) Spray a calcium gluconate solution 0.02 times the volume of the hydrogel on the surface of the sodium alginate-PEDOT:PSS-calcium ion hydrogel. After cross-linking for 3 seconds, demold the gel, rinse the surface with deionizer, and use filter paper to absorb the moisture on the surface of the hydrogel to obtain a sodium alginate polysaccharide conductive polymer material (SA-Ca-PEDOT:PSS / Ca).
[0091] The polymer material prepared above was tested by scanning electron microscopy and energy dispersive X-ray spectrometer; the properties of the polymer material were verified by swelling rate test, mechanical property test, rheological property test, electrical conductivity test and wound healing test. In the example, alginate calcium chloride hydrogel was used as a comparison, and its preparation method was to replace 0.2 parts by mass of calcium carbonate in the component of Example 1 with calcium chloride with the same calcium ion concentration, and the rest of the operations were the same.
[0092] (1) pH detection
[0093] The pH value of the system was tested before and after the addition of calcium carbonate to the alginate polysaccharide conductive polymer material. The pH (SA-PEDOT:PSS-Ca / Ca) was determined by soaking the SA-PEDOT:PSS-Ca / Ca hydrogel in deionized water for 12 hours and then measuring the pH of the deionized water. The pH determination method of the alginate calcium chloride hydrogel was the same as that of the SA-PEDOT:PSS-Ca / Ca. The results are shown in Table 1.
[0094] Table 1
[0095] Sample pH SA-PEDOT:PSS SA-PEDOT:PSS-Ca / Ca Calcium chloride alginate Example 1 3.06±0.02 6.96±0.02 5.74±0.02 Example 2 3.40±0.01 7.46±0.01 5.92±0.02 Example 3 3.58±0.02 6.92±0.03 5.22±0.01
[0096] As can be seen from the table, the SA-PEDOT:PSS-Ca / Ca hydrogel of the present invention effectively solves the acidity problem caused by PEDOT:PSS in the existing SA-PEDOT:PSS hydrogel by using calcium carbonate, and is more suitable for the preparation of wound healing materials.
[0097] (2) Scanning electron microscope (SEM) inspection
[0098] The alginate polysaccharide conductive polymer material and alginate calcium chloride hydrogel obtained in Example 1 were submerged, quenched, and brittlely broken. After freeze-drying, they were cut into regular and appropriate sizes. The brittlely broken alginate polysaccharide conductive polymer material was attached to a copper table with conductive glue and covered with gold spray. The microscopic morphology was observed using SEM, and the alginate calcium chloride hydrogel was used as a comparison. The test results are as follows: Figure 1-Figure 2 shown. Figure 1 This is a scanning electron microscope image of the alginate polysaccharide conductive polymer material prepared in Example 1 of the present invention. Figure 2 This is a scanning electron micrograph of alginate-calcium chloride hydrogel.
[0099] As can be seen from the figure, the alginate polysaccharide conductive polymer material of the present invention has a continuous microporous structure. These evenly distributed holes make the obtained hydrogel present a uniform and loose structure inside and outside, ensuring the hydrogel's strong water absorption and water retention capacity, and having the characteristics of a cytoplasmic matrix. At the same time, the pore size in the hydrogel promotes the migration of ions in the pores, thereby enhancing its conductivity. The pore structure of alginate calcium chloride hydrogel is less and uneven.
[0100] (3) Energy dispersive X-ray spectrometer (EDS) element analysis
[0101] Take the alginate polysaccharide conductive polymer material obtained in Example 1, submerge it, quench it, break it, freeze-dry it, and cut it into regular and appropriate sizes. Use conductive glue to stick the broken alginate polysaccharide conductive polymer material on a copper table and spray gold to cover it. Perform EDS scanning to analyze the types and contents of chemical elements in the selected area. The test results are as follows: Figure 3 As shown in the figure, it can be seen that the elements are uniformly dispersed in the alginate polysaccharide conductive polymer material. C and O elements come from organic matter, Na element comes from sodium alginate, Ca element comes from calcium carbonate, and S element is a representative element of PEDOT:PSS, indicating that the conductive material PEDOT:PSS is uniformly dispersed in the alginate polysaccharide conductive polymer material.
[0102] (4) Swelling rate test
[0103] Take the alginate polysaccharide conductive polymer material prepared in Example 1 and weigh the initial mass M 0 , put it into a 50mL centrifuge tube, three parallel samples for each group of samples, add 10mL of PBS buffer with pH=7.4 to each centrifuge tube, and place the centrifuge tube in a 37℃ constant temperature shaker (150rpm). Take it out at different time points, absorb the surface water and weigh it. When the mass of the hydrogel does not change much, record it as M s The calculation formula of the swelling rate (S) of the sample is: S% = (M s -M 0 ) / M 0 × 100%. The results of the swelling rate test are shown in Figure 4 . Among them, a is the swelling curve of the alginate polysaccharide conductive polymer material prepared in Example 1, and b is the swelling curve of the alginate calcium chloride hydrogel. It can be seen from the figure that the alginate polysaccharide conductive polymer material of the present invention reaches swelling equilibrium in 12 hours, and the swelling rate is 120%, which means that the hydrogel can effectively absorb exudate and maintain its shape without being quickly released, ensuring that the moisture content of the wound bed is appropriate to promote wound healing. The alginate calcium chloride hydrogel reaches swelling equilibrium in 8 hours, and the swelling rate is 58%.
[0104] (5) Cyclic compression curve
[0105] Take the alginate polysaccharide conductive polymer material prepared in Example 1, with at least three parallel samples for each group of samples, place the samples on a testing machine, compress the samples at a rate of 3mm / min, and the maximum compression deformation is 60%. The cyclic compression is the same as the ordinary compression experiment, and the cyclic compression is repeated 5 times. The values of stress and strain are recorded starting from the compression displacement of zero, and the compression stroke is 60%. The displacement and load obtained by the test are used to calculate the strain and stress, and the stress-strain curve is obtained. Calculation formula: σ=4F / D 2; ε=ΔL / L; where σ is stress, ε is strain, F is load, D is sample diameter, ΔL is displacement, L is sample thickness, and three samples are tested in each group. The results of the cyclic compression curve are shown in Figure 5 As can be seen from the figure, the alginate polysaccharide conductive polymer material of the present invention still has good resilience after being compressed five times, indicating that it can provide auxiliary pressure to the wound surface, help stop bleeding, and avoid squeezing the wound surface.
[0106] (6) Strain scanning curve
[0107] The alginate polysaccharide conductive polymer material prepared in Example 1 was placed on the rheometer platform for strain scanning test at a frequency of 1 Hz and a time of 25°C. The results of the strain scanning curve are shown in FIG. Figure 6 As shown in the figure, it can be seen that in the strain scanning mode, as the strain increases, G' is always greater than G", and the hydrogel will reach the critical point of G'=G" by continuously applying a greater strain to the gel; when the strain is greater than 28.39%, G' and G" begin to decrease, and the decrease rate of G' is greater than that of G', indicating that the alginate polysaccharide conductive polymer material has appropriate mechanical properties and viscoelasticity, and its flexibility is conducive to covering irregular wound surfaces.
[0108] (7) Alternating strain scanning curve
[0109] The alginate polysaccharide conductive polymer material prepared in Example 1 was placed on the rheometer platform for an alternating strain scanning test, with a small strain of 1%, a large strain of 200%, a frequency of 1 Hz, and a time of 25°C. The results of the alternating strain scanning curve are shown in FIG. Figure 7 As shown in the figure, it can be seen that under low strain, G' of the alginate polysaccharide conductive polymer material is always higher than G", and under higher strain, G" is always higher than G', and after three cycles, G' and G" can still recover quickly, indicating that the alginate polysaccharide conductive polymer material has good self-healing properties.
[0110] (8) Electrical performance test
[0111] Take the alginate polysaccharide conductive polymer materials prepared in Example 1, Example 2 and Example 3, with at least three parallel samples for each group of samples. Connect both sides of the hydrogel to a multimeter, measure the IV curve, calculate the resistance of the hydrogel by Ohm's law, and then obtain the conductivity. Formula: R=U / I; ρ=R×A / L; σ=1 / ρ=L / RA; wherein R is resistance, U is voltage, I is current, ρ is resistivity, A is the cross-sectional area of the hydrogel, L is the length of the hydrogel, and σ is the conductivity of the hydrogel. The electrical performance results are shown in the figure. Figure 8 As shown in the figure, the conductivity of the alginate polysaccharide conductive polymer material of the present invention is 1.46×10 -3, 5.35×10 -4 and 1.99×10 -3 S / cm, the conductivity of human skin is 2.6×10 -3 to 1×10 -7 S / cm, and the matching of the conductivity with the normal skin conductivity helps to maximize the application of current to the damaged tissue, thereby increasing the healing effect of the wound. The results show that the alginate polysaccharide conductive polymer material of the present invention has suitable electrical properties for promoting wound healing.
[0112] (9) Wound healing test results
[0113] SPF male Sprague-Dawley (SD) rats aged 6 to 8 weeks were selected and randomly divided into 6 groups, with 3 rats in each group. They were housed individually in ventilated cages at a temperature of (21±2)℃ and a relative humidity of (55±10)%, with free access to food and water. After the rats were anesthetized by intraperitoneal injection of 20mg / mL sodium pentobarbital (dose of 2mL / kg), they were depilated with a razor and depilatory cream to completely expose the back. The surgical area was disinfected with 75% ethanol, and the skin of the rat was gently lifted. Then, a magnet with a diameter of 2.0cm was used to clamp the skin to cause local ischemic pressure. The pressure state was maintained for 12 hours, and then the magnet was removed to allow the skin to restore blood flow for 12 hours. This was repeated for 3 to 4 consecutive days to form ischemic ulcers. All animal experiments were performed in a specific pathogen-free environment. After the pressure sore modeling was successful, medical bandages and commercial Tegaderm (3M, 1624WB) films were used as negative and positive control groups, respectively. The experimental groups were ES alone, SA-Ca-PEDOT:PSS / Ca (gel group in Example 1), ES+SA-Ca-HCL / Ca, and ES+SA-Ca-PEDOT:PSS / Ca. ES was to place two platinum electrodes connected to a DC power supply on both sides of the wound every day, and apply an electric field of 100mV / mm for 30 minutes. After the electrical stimulation was completed, a multimeter was used to monitor the wound resistance. The dressing and bandage were removed every day, and the wound was gently scrubbed and debrided with saline and cotton swabs. All materials were fixed to the injured area with elastic bandages and fixed with medical bandages for the second time. The wound was photographed with a camera at 0, 3, 7, and 10 days, and the wound area was calculated with ImageJ software. The degree of wound healing was calculated by the percentage of wound area contraction (WA): WA (%) = At / A0 × 100%; where A0 is the initial wound area; At is the wound area on day t. Fig. 9 As shown in the figure, it can be seen that the alginate polysaccharide conductive polymer material of the present invention can significantly promote wound healing.
[0114] In summary, the present invention provides an alginate polysaccharide conductive polymer material, which has the effect of promoting wound healing. At the same time, the main raw material sources of the material preparation method of the present invention are wide, the cost is low, the synthesis conditions are mild, the production route is simple, the process flow is simple, the operability is strong, the production quality is easier to control, and compared with existing similar products, it has safety and clinical use value.
[0115] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. An alginate polysaccharide conductive polymer material, characterized in that The composite is obtained by cross-linking sodium alginate, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate and calcium carbonate.
2. The alginate polysaccharide conductive polymer material according to claim 1, characterized in that The mass ratio of the sodium alginate, poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate and calcium carbonate is (5-30):(1-13):(0.5-4).
3. The alginate polysaccharide conductive polymer material according to claim 1, characterized in that The content of sodium alginate in the material is 0.5-3.0wt%.
4. The alginate polysaccharide conductive polymer material according to claim 1, characterized in that: The polymerization degree of the sodium alginate is 80-750.
5. The alginate polysaccharide conductive polymer material according to claim 1, characterized in that A calcium ion solution is further coated on the surface of the gel for further cross-linking, thereby obtaining a hydrogel with further cross-linked surface.
6. The alginate polysaccharide conductive polymer material according to claim 1, characterized in that: The concentration of calcium ions in the calcium ion solution is 0.05-0.6 mol / L.
7. A method for preparing the alginate polysaccharide conductive polymer material according to any one of claims 1 to 6, characterized in that The method comprises mixing sodium alginate, poly (3, 4-ethylenedioxythiophene) -polystyrene sulfonate and calcium carbonate in a water system to obtain a mixed solution, placing the mixed solution in a mold for cross-linking to obtain a sodium alginate-PEDOT:PSS-calcium ion hydrogel.
8. The preparation method according to claim 7, characterized in that: In the mixed solution, the mass concentration of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate is 1g / L-13g / L; the mass concentration of calcium carbonate is 0.5g / L-4g / L.
9. The preparation method according to claim 7, characterized in that After the sodium alginate-PEDOT:PSS-calcium ion hydrogel is obtained by cross-linking in the mold, a calcium ion solution with a calcium ion concentration of 0.05-0.6 mol / L is coated on the surface of the hydrogel, and after static cross-linking, an alginate polysaccharide conductive polymer material with further cross-linking on the surface is obtained.
10. Use of the alginate polysaccharide conductive polymer material according to any one of claims 1 to 6 in the field of chronic wound healing and tissue regeneration.
Citation Information
Patent Citations
Biomimetic electronic skin medical stent material with self-repairing function and preparation method thereof
CN111825859A
Cotton gauze enhanced hydrogel conductive dressing with photo-thermal antibacterial and healing promoting effects and preparation method thereof
CN113694244A
Sodium alginate and PEDOT: PSS mixed conductive hydrogel, preparation method and application method thereof
CN113801343A
Substrate for a three-dimensional cell culture, its preparation and use
US20170166862A1
Self-healing electroconductive hydrogels, their composition, uses, and methods of production
WO2024162863A1